PENDIDIKAN ISLAM ALTERNATIF, SEBUAH PENDEKATAN KULTURAL (Analisis atas pemikiran Abdurrahman Wahid) - As’ari, Kasan; Sholihah, Hidayatus (Universitas Islam Sultan Agung, 2018)
This article is based on the library reseach using an analysis content. This research is trying to analyse an Islamic education based on Abdurrahman wahid or Gus Dur’s thought, before he was elected as the fourt President of RI periode, from 1970 to 1998. This essay is based on the text written by Gus Dur, whether in the form of books, articles, newspaper section and any other types of the text , and also the papers from other figures who tried to interprete his thought. Based on Abdurrahman Wahid, the unclear national education direction programmed by the government - since colonial period until the reform era , that did not eliminate the colonial era heritage - is to create